PEMETAAN LAHAN DAN KOMODITAS PERTANIAN BERBASIS WEBGIS DI KABUPATEN OKU TIMUR - Andi Santoso; Muhammad Nasir (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
Abstract: The potential of agricultural land in Indonesia is still very wide so that the agricultural sector is still one of the incomes for most Indonesian people. The agricultural land sector is widely distributed in various regions in Indonesia, one of which is in the East Oku Regency, South Sumatra. As an agricultural area, the majority of the population in East Oku Regency choose their livelihood as farmers. However, the distribution of agricultural land has not been mapped, which can provide information about the location of agricultural land, especially in East Oku Regency. In this study, the development of a web-based Agricultural Land Geographic Information System in East OKU Regency was carried out. The geographic information system built can display information in the form of spatial and non-spatial data that describes an object based on the state of the earth. The method used in making this system is object-oriented method. With the development of this Geographic Information System, it is hoped that it will be able to provide information for the community about the distribution of the location and area of ​​agricultural land, especially in the East OKU Regency area.